2018
DOI: 10.1002/met.1721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trends in rainfall and dry/wet years over a century in the Eastern Ganga Canal command

Abstract: In the present study, an attempt has been made to analyse the variability and trends in annual and seasonal rainfall over the Eastern Ganga Canal command area, India. To determine the trend in annual/seasonal rainfall and rainy days, the non‐parametric Mann−Kendall test and Sen's slope method were used over daily gridded rainfall for the time period 1901–2012. The results of the trend analysis revealed a decreasing trend in annual and monsoon rainfall in the range 18.5−61.7 and 19.4−56.7 mm/decade, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The average annual rainfall of the Yuqiao Reservoir Watershed is 709.2 mm. To separate the dry, wet, and normal years, deviation (≥25%) from the mean annual rainfall was used to create them, meaning that a negative deviation can be defined as dry years and a positive deviation is termed as wet years [ 45 ]. Therefore, three continuous years—2019 (−31.5%), 2020 (4.7%), and 2021 (34.7%)—were selected for further analysis as the representatives of dry, normal, and wet years, respectively, which may minimize the potential effect from the land use change compared to a large time interval.…”
Section: Methodsmentioning
confidence: 99%
“…The average annual rainfall of the Yuqiao Reservoir Watershed is 709.2 mm. To separate the dry, wet, and normal years, deviation (≥25%) from the mean annual rainfall was used to create them, meaning that a negative deviation can be defined as dry years and a positive deviation is termed as wet years [ 45 ]. Therefore, three continuous years—2019 (−31.5%), 2020 (4.7%), and 2021 (34.7%)—were selected for further analysis as the representatives of dry, normal, and wet years, respectively, which may minimize the potential effect from the land use change compared to a large time interval.…”
Section: Methodsmentioning
confidence: 99%
“…During the winter, summer, monsoon, and postmonsoon seasons, the magnitudes of rainfall trends with a corresponding value of Sen's estimator are 0.5, 2.137, 6.901, and −2.276 mmÁyear −1 , F I G U R E 1 (a) Location of Andhra Pradesh State (shaded area in the red square) in India (b) the elevation (m) map of southern peninsular India (SRTM DEM, 3 arcsec) and the pink "*" represents the geographical location of the measurement site respectively, with a 90% of the significance level. The variability in rainfall affects water supply at different stages of crop development to meet the crop water demand (Krishan et al, 2018).…”
Section: Temporal Trends Of Temperature and Rainfallmentioning
confidence: 99%
“…(2014) conducted change detection study on climatic parameter over Raipur district of India and found significant rising trend in summer temperature with rising evaporation process attributed to increased wind speed and temperature. Krishan et al (2017) analysed the trends in rainfall and dry/wet years over a canal command area of Northern India. Study found a significant decreasing trend in annual and monsoon rainfall.…”
Section: Introductionmentioning
confidence: 99%